Study on micropillar arrangement optimization of wireless-electrodeless quartz crystal microbalance sensor and application to a gas sensor. (8th March 2021) - Kato, Fumihito; Sato, Yu; Ato, Hiroki; Kuwabara, Haruki; Kobayashi, Yuto; Nakamura, Kensuke; Masumoto, Noriyasu; Noguchi, Hiroyuki; Ogi, Hirotsugu
Abstract: This paper studies the structural design of the wireless-electrodeless quartz crystal microbalance (QCM) sensor, which has a rectangular AT-cut quartz oscillator installed in the microchannel fabricated by nanoimprint lithography. The quartz oscillator was supported by the micropillars in the microchannel, and by optimizing the micropillar arrangement, it was found that the structural damping could be significantly reduced by performing the finite elemental piezoelectric analysis. This behavior was then confirmed by the experiments using the evaluation chips. By supporting the four corners of the quartz oscillator with the micropillars, the structural damping could be reduced, achieving a high-quality factor ( Q -factor) of about 24700. This high Q -factor was also realized in the experiments, and we investigated its application to a hydrogen-gas sensor. We succeeded in detecting hydrogen gas with an extremely low concentration of 10 ppm.